Spontaneous fistulisation of the common bile duct after transection by gunshot. Issue 2 (4th February 2021) - Howard, Jessica; Di Sano, Suzanne; Burnett, David
Abstract : A 35-year-old man presented with a gunshot wound to his abdomen via his lower chest. Initial laparotomy did not identify any perforation or contamination. On day 3, a laparotomy under the hepatobiliary service discovered a gastric perforation, two lateral duodenal perforations and a complete transection of the common bile duct, presumably delayed perforation from the shockwave injury produced by the bullet. Contamination and haemodynamic instability precluded immediate reconstruction, and abdominal drains and external biliary drainage were established. High-volume duodenal fistula was managed with slow withdrawal of drains, and inadvertent dislodgement of the biliary drain in an outpatient setting resulted in spontaneous fistulisation of the bile duct to the lateral duodenal wall, with creation of a neo-bile duct. The patient remains well more than 1 year later, without external drainage despite no surgical reconstruction.